The filmmaker's eye learning (and breaking) the rules of cinematic composition - Mercado, Gustavo (Focal Press/Elsevier, 2011)
This is the only book that combines conceptual and practical instruction on creating polished and eloquent images for film and video with the technical know-how to achieve them. Loaded with hundreds of full-color examples, "The Filmmaker's Eye" is a focused, easy-to-reference guide that shows you how to become a strong visual storyteller through smart, effective choices for your shots. This book has struck a chord worldwide and is being translated into several languages After a short introduction to basic principles, a variety of shots are deconstructed in the following format: - Why It Works: an introduction to a particular type of shot - How It Works: callouts point out exactly how the shot works the way it does--the visual rules and technical aspects in action - Technical Considerations: the equipment and techniques needed to get the shot. - Breaking the Rules: examples where the "rules" are brilliant subverted * Make smart visual choices with this quick, focused, and visual guide to cinematic composition. * Shows you how to master the rules, then break them. * Includes examples and discussions from a range of international films